Seasonal variation in objectively assessed physical activity among children and adolescents in Norway: a cross-sectional study - Andersen Lars B; Steene-Johannessen Jostein; Kolle Elin; Anderssen Sigmund A (BMC, 2009)
Abstract Background The literature on seasonality in children and youth's physical activity participation is inconsistent. The aims of this study were to: 1) compare physical activity across seasons and describe activity patterns within seasons, and 2) to determine compliance with current physical activity recommendations across seasons among 9- and 15-year-olds living in a climatically diverse country. Methods Participants were 2,299 9- and 15-year-olds from all regions in Norway. Physical activity was assessed using the Actigraph accelerometer for 4 consecutive days. Physical activity data were collected during winter, spring and fall. General linear models were used to study the associations between physical activity and season. Results Nine-year-old children had significantly higher mean physical activity levels in spring than in winter and fall. In the two latter seasons, physical activity levels were especially low after school hours and on weekends. Logistic regression models demonstrated that 9-year-olds had 3.3 times (95% Confidence Interval (CI): 2.08, 5.18) higher odds of meeting recommended levels of physical activity in spring than in winter. No associations were found between mean physical activity level and season among the 15-year-olds. However, the adolescents also had higher odds (OR = 1.56; 95% CI: 1.05, 2.32) of meeting the physical activity recommendations in spring than in winter. Conclusion In a large population-based sample, we observed substantial seasonal differences in physical activity among 9-year-olds, and the activity pattern varied across the seasons. The results emphasize the need to take season into account when developing physical activity interventions for children. Season appears to have less influence on adolescent's physical activity; interventions for increasing physical activity in this group could therefore be implemented throughout the year.